Duodenal ulcer perforation with ileal perforation in the same patient: A Case Report - Sharma Subedi, Sushil; Acharya, Sabanam; Raj Gautam, Bodh; Neupane, Durga (Nepal Journal of Medical Sciences, 2025)
There are no documented case reports from our country describing a patient with both a duodenal ulcer perforation and an ileal perforation. Here we present a 60-year-old, alcoholic and smoker, presented with a complaint of abdominal pain for 10 days. On examination, vitals were deranged with tachycardia and hypotension and tense and tender abdomen with absent bowel sounds. The patient was resuscitated and shifted to theatre for exploration with provisional diagnosis of perforated duodenal ulcer. A 5×5 mm perforation on the first part of the duodenum along with a 10×10 mm perforation on antimesenteric surface of ileum that is 100 cm proximal to ileocecal junction was noted. Graham’s patch repair was carried out for duodenal perforation, while exteriorization of perforated ileal segment was made for ileal perforation. Multiple perforations of hollow organs can occur in a single patient, which if not identified, could lead to catastrophic events.